Bioseparation engineering : proceedings of an International Conference on Bioseparation Engineering : "Recovery and Recycle of Resources to Protect the Global Environment, " organized under the Special Research Group on Bioseparation Engineering in the Society of Chemical Engineers, Japan, Nikko, Japan, July 4-7, 1999 /: proceedings of an International Conference on Bioseparation Engineering : "Recovery and Recycle of Resources to Protect the Global Environment, " organized under the Special Research Group on Bioseparation Engineering in the Society of Chemical Engineers, Japan, Nikko, Japan, July 4-7, 1999. (2000) - Unknown
No abstract available